1988
DOI: 10.1029/jd093id06p07119
|View full text |Cite
|
Sign up to set email alerts
|

Relative quantum yield of O(1D2) following ozone photolysis between 275 and 325 nm

Abstract: Relative values of the quantum yield of O(XD2) from the photolysis of ozone in the wavelength region 275-325 nm have been measured by observing infrared fluorescence following the reaction O(XD2) -3-CO2--•O(3pj)-3-C02((mnp), indicating multiply vibrationally excited CO 2 with m quanta in the symmetric mode v x, n in the (doubly degenerate) bend v 2, and p in the asymmetric stretch %)), using the frequency-doubled output of a narrow-band dye laser as the photolysis source. The location and shape of the falloff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
43
1
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 17 publications
10
43
1
1
Order By: Relevance
“…late their results but their reported yields are in very close agreement with the yields of Trolier and Weisenfeld [16]. Recent measurements of Ball and coworkers [17][18][19] show that the yield of O2(~A) is significant out to 325 nm.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…late their results but their reported yields are in very close agreement with the yields of Trolier and Weisenfeld [16]. Recent measurements of Ball and coworkers [17][18][19] show that the yield of O2(~A) is significant out to 325 nm.…”
Section: Discussionsupporting
confidence: 78%
“…Early experiments on the yield of O ID were reviewed by Steinfeld et al [1]. Those workers recommended a 'tail' in @O'D based on the laser photolysis experiments of Brock and Watson [15] and Trolier and Weisenfield [16]. However, both the NASA and IUPAC panels have continued to regard this tail as an artifact.…”
Section: Discussionmentioning
confidence: 99%
“…Talukdar et al (1998) reported that the O( 1 D) quantum yield between 289 and 305 nm was 0.89±0.02, which is in good agreement with results presented by Taniguchi et al (2000) and Takahashi et al (2002). The yield values reported by Trolier and Wiesenfeld (1988) and JPL-2000 recommendations in this wavelength region are larger than values reported by Talukdar et al (1998) , Taniguchi et al (2000), and Takahashi et al (2002). At shorter wavelengths, JPL-2000 panel has recommended a constant value of 0.95 for the O( 1 D) quantum yield in the Hartley band photolysis of O 3 between obtained by Taniguchi et al (2000) and Takahashi et al (2002).…”
Section: Introductionsupporting
confidence: 81%
“…In Fig. 2, the yield values presented by Taniguchi et al (2000) and Takahashi et al (2002) are compared with both values previously reported by other different groups (Trolier and Wiesenfeld, 1988;Cooper et al, 1993;Talukdar et al, 1997Talukdar et al, , 1998 and JPL-2000 recommendations . Talukdar et al (1998) reported that the O( 1 D) quantum yield between 289 and 305 nm was 0.89±0.02, which is in good agreement with results presented by Taniguchi et al (2000) and Takahashi et al (2002).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation